2015
DOI: 10.1088/0004-637x/805/1/51
|View full text |Cite
|
Sign up to set email alerts
|

A Megacam Survey of Outer Halo Satellites. Iv. Two Foreground Populations Possibly Associated With the Monoceros Substructure in the Direction of NGC 2419 and Koposov 2

Abstract: The origin of the Galactic halo stellar structure known as the Monoceros Ring is still under debate. In this work, we study this halo substructure using deep Canada-France-Hawaii Telescope wide-field photometry obtained for the globular clusters NGC 2419 and Koposov 2, where the presence of Monoceros becomes significant because of their coincident projected position. Using Sloan Digital Sky Survey photometry and spectroscopy in the area surrounding these globulars and beyond, where the same Monoceros populatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…For a number of these clusters, secondary main sequences are observed beyond the cluster's extent. In some cases, such as NGC2419 and Kop 2, the extra main sequences lie in the background or foreground of the clusters (Carballo-Bello et al 2015). In other cases, like the ones presented here, the sequences seem to be at the same distance of the clusters, indicating either the presence of an extended structure related to the cluster (i.e., tidal tails or extended halos) or revealing the existence of a stream within which the clusters lie.…”
Section: Resultssupporting
confidence: 50%
“…For a number of these clusters, secondary main sequences are observed beyond the cluster's extent. In some cases, such as NGC2419 and Kop 2, the extra main sequences lie in the background or foreground of the clusters (Carballo-Bello et al 2015). In other cases, like the ones presented here, the sequences seem to be at the same distance of the clusters, indicating either the presence of an extended structure related to the cluster (i.e., tidal tails or extended halos) or revealing the existence of a stream within which the clusters lie.…”
Section: Resultssupporting
confidence: 50%
“…Even so, it is striking that despite several indications that both Eridanus and Pal 15 might be accreted, and our data being sensitive enough to detect low surface brightness features at their distances, no clear evidence for stellar debris from parent dwarf galaxies was observed. Carballo-Bello et al (2015) suggested that Eridanus may be associated with the Monoceros ring based on the modelled orbit of this structure by Penarrubia et al (2005); however, the great circle of Eridanus disagrees with this modelled orbit, suggesting no clear association between them.…”
Section: Discussionmentioning
confidence: 98%
“…This survey presents unprecedented photometric data quality for describing an almost complete sample of outer halo satellites, which was already used in many published works (see e.g. Bradford et al 2011;Sollima et al 2011a,b;Santana et al 2013;Carballo-Bello et al 2015). The camera Megacam at CFHT is a prime focus mosaic camera consisting of thirty-six 2048 × 4612 pixel CCDs (a total of 340 megapixels), covering a 0.…”
Section: O B S E Rvat I O Na L M At E R I a Lmentioning
confidence: 99%